Research on the high-quality development of sports-tourism integration in healthy cities under international events--Taking the 19th Hangzhou Asian Games as an example - Ye, Yangyang; Ding, Yuliang; Xu, Meiqi (Transactions on Economics, Business and Management Research, 2024)
With the continuous promotion of the national policy of "Healthy China" strategy, the construction of healthy cities has become one of the important contents of China's urban development, and the integrated development of sports and tourism \has also entered a new stage of high-quality promotion. This paper focuses on the healthy city development of Hangzhou, aiming at the international event node of the Asian Games, from the actual development of Hangzhou's sports tourism, the exploration in digitization, integration, branding, nationalization and low-carbon development, and provides practical reference for the long-term development of sports tourism in other countries and regions.